Symbolic Dynamics and Chaotic Synchronization in Coupled Duffing Oscillators - Caneco, Acilina (2014)
In this work we discuss the complete synchronization of two identical double-well Dufﬁng oscillators unidirectionally coupled, from the point of view of symbolic dynamics. Working with Poincar´e cross-sections and the return maps associated, the synchronization of the two oscillators, in terms of the coupling strength, is characterized. We obtained analytically the threshold value of the coupling parameter for the synchronization of two unimodal and two bimodal piecewise linear maps, which by semi-conjugacy, under certain conditions, gives us information about the synchronization of the Dufﬁng oscillators.